2022
DOI: 10.1038/s12276-022-00736-w
|View full text |Cite
|
Sign up to set email alerts
|

The mechanism of HMGB1 secretion and release

Abstract: High mobility group box 1 (HMGB1) is a nonhistone nuclear protein that has multiple functions according to its subcellular location. In the nucleus, HMGB1 is a DNA chaperone that maintains the structure and function of chromosomes. In the cytoplasm, HMGB1 can promote autophagy by binding to BECN1 protein. After its active secretion or passive release, extracellular HMGB1 usually acts as a damage-associated molecular pattern (DAMP) molecule, regulating inflammation and immune responses through different recepto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
172
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 411 publications
(244 citation statements)
references
References 247 publications
5
172
1
Order By: Relevance
“…Partially reduced HMGB1, also termed disulfide-HMGB1, carries a disulfide bond between C23 and C45, and can trigger inflammatory responses [ 111 ]. Once released into the extracellular space, reduced HMGB1 potentiates the inflammatory response through different mechanisms [ 112 , 113 ]. It is able to induce neutrophil recruitment to the site of injury [ 114 ], bind directly to PRRs such as RAGE, TLR2, TLR4, TLR9, and triggering receptor expressed in myeloid cells 1 (TREM1) [ 59 , 62 , 63 , 64 , 65 , 66 ], but also bind to PAMPs such as LPS [ 115 ], DNA [ 116 ] or lipoteichoic acid [ 117 ].…”
Section: Damps Associated With Nets or Capable Of Inducing Netsmentioning
confidence: 99%
See 1 more Smart Citation
“…Partially reduced HMGB1, also termed disulfide-HMGB1, carries a disulfide bond between C23 and C45, and can trigger inflammatory responses [ 111 ]. Once released into the extracellular space, reduced HMGB1 potentiates the inflammatory response through different mechanisms [ 112 , 113 ]. It is able to induce neutrophil recruitment to the site of injury [ 114 ], bind directly to PRRs such as RAGE, TLR2, TLR4, TLR9, and triggering receptor expressed in myeloid cells 1 (TREM1) [ 59 , 62 , 63 , 64 , 65 , 66 ], but also bind to PAMPs such as LPS [ 115 ], DNA [ 116 ] or lipoteichoic acid [ 117 ].…”
Section: Damps Associated With Nets or Capable Of Inducing Netsmentioning
confidence: 99%
“…Following ischemia–reperfusion of the kidney, neutrophils infiltrate the lung, increasing cytokine secretion, and NET formation, which was ameliorated upon PAD4 inhibition, thereby reducing ischemia–reperfusion-consecutive lung injury [ 159 ]. Doi and colleagues [ 160 ] revealed that ALI following AKI depends on HMGB1, which is further underlined by a recently published study demonstrating that acute lung injury following intestinal ischemia–reperfusion depends on HMGB1-induced NET formation, associated with tissue inflammation, and pathological injury in the lung [ 112 , 161 ]. In line with this, histones have detrimental effects on alveolar cells in vitro and in vivo during transfusion-related lung injury [ 75 , 162 ].…”
Section: Organ Dysfunction and Remote Organ Injurymentioning
confidence: 99%
“…The activity of extracellular HMGB1 is regulated not only by the receptor, but also by its redox state and structure. In addition to the nuclear and extracellular roles of HMGB1, cytoplasmic HMGB1 could bind many proteins involved in autophagy, cancer evolution and unconventional secretory pathways ( 35 ).…”
Section: High Mobility Group Proteinsmentioning
confidence: 99%
“…Rather than reducing their immune response to DAMPs over time, their immune system may have a prolonged inflammatory activation by DAMPs such as HMGB1 and therefore release pro-inflammatory cytokines in response to chronic stress (Figure 1). Inflammatory cytokines and LPS also upregulate HMGB1 expression and secretion from macrophages, further increasing circulating HMGB1 (Chen et al, 2022). This may not cause much damage during a short stressful experience, but if a patient is producing pro-inflammatory cytokines such as TNF-α over a long period of chronic stress lasting months or years, it is possible that significant damage could be caused.…”
Section: Stress-induced Immune Activationmentioning
confidence: 99%